Transformational leadership in Yemen customs - AL-ABSI, Maher Othman Abdo Mohammed (KDI School, 2015)
The relationship between transformational leadership and organizational change is widely covered in different ways in the literature. This study covered the role of the transformational leadership in organizational change in Yemen Customs. The researcher hypothesized a positive relationship between the transformational leadership and organizational change and used questionnaire to collect a data from 176 employees of Yemen Customs to measure this relation. After calculating the data through a regression analysis, the results supported the hypothesis. In addition to this, the descriptive analyses for the data shows that both transformational leadership and organizational change management are weak in Yemen Custom.
Thesis(Master) --KDI School:Master of Public Policy,2015